A Review on Heat Transfer Enhancement of Borehole Heat Exchanger. (December 2016) - Zhao, Jun; Li, Yang; Wang, Junyao
Abstract: The heat transfer enhancements of borehole heat exchanger (BHE) have been intensively studied which strongly influences the performance of ground-coupled heat pump (GCHP) systems. In this paper, some typical heat transfer enhancement methods of BHE are reviewed based on BHE designs, grout materials and the influence of artificial groundwater flow. Features and feasibility of different methods have been discussed for the different applications.